2008
DOI: 10.1007/s00339-008-4800-z
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced decoration of carbon nanotubes with metal nanoparticles

Abstract: Hybrid nanomaterials consisting of multiwall carbon nanotubes (MWCNT) decorated with noble metal nanoparticles were produced by irradiating aqueous mixed solutions of the separate components with nanosecond lasers pulses at 248 nm. Specifically, the decoration with Au and Pd nanoparticles is discussed. No decoration of the MWCNT was observed by simple mixing with nanoparticle solutions. Hence, a photo-thermal mechanism is suggested, whereby the laser-heating of the nanoparticles induces melting, boiling and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…In addition, several reports have appeared describing the synthesis of bimetallic particles, such as Au-Ag bimetallic nanoparticles. As shown in the literature, Link et al [26] reported a method to form gold-silver alloy nanoparticles. In their study, gold-silver alloy nanoparticles can be grown by coreduction of chlorauric acid and silver nitrate with sodium citrate in aqueous solutions.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, several reports have appeared describing the synthesis of bimetallic particles, such as Au-Ag bimetallic nanoparticles. As shown in the literature, Link et al [26] reported a method to form gold-silver alloy nanoparticles. In their study, gold-silver alloy nanoparticles can be grown by coreduction of chlorauric acid and silver nitrate with sodium citrate in aqueous solutions.…”
Section: Introductionmentioning
confidence: 96%
“…Among various growth methods, we have used a simple physical co-sputtering method. The flexibility and easy fabrication of diverse composite films with uniformly distributed metal particles and various metal-dielectric combinations are the other advantages of sputtering method [5,26,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of these two materials may lead to a successful integration of their properties in new hybrid materials that may be useful in catalysis, nanoelectronics, optics and nanobiotechnology [105][106]. Carbon nanotubes have been decorated with metal nanoparticles of Au, Ag, Pt, Pd and Co employing different procedures such as the click reaction [107], microwave treatment [106], electroless plating [108] and laser irradiation of mixtures of the individual components [109]. Pt-carbon nanotube hybrids have been used as catalysts for the conversion of nitrobenzene to aniline [110].…”
Section: Graphene-inorganic Nanoparticle Hybridsmentioning
confidence: 99%
“…Pd nanoparticles were produced by pulsed laser ablation process [16]. The average size of the particles were around 5-10nm.…”
Section: B Sample Preparationmentioning
confidence: 99%